2020
DOI: 10.1007/s00240-020-01206-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hemoglobin as a quantifiable indicator of renal arterial embolization in post-percutaneous nephrolithotomy hemorrhage

Abstract: To determine quantifiable indicators for post-percutaneous nephrolithotomy (PCNL) renal arterial embolization. A total of 2043 patients who underwent PCNL from September 2012 to March 2018 were reviewed retrospectively. Post-operative hemorrhage patients were extracted and divided into two groups according to treatment methods (conservative methods or super-selective renal arterial embolization [SRAE]). Demographic characteristics and hemorrhage outcomes were compared between the two groups by univariable anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“… 29 , 30 Anemia can also induce oxidative stress through endothelial damage. 31 , 32 In our study, decrease in Hb level was strongly associated with the decrease in cognitive function of patients in the CI group as compared to patients without cognitive impairment. Pearson correlation analysis in our study showed that in ischemic stroke patients, the serum APN and Hb levels were positively correlated with MOCA scores, indicating a linear relationship between serum APN and Hb levels and vascular cognitive impairment severity.…”
Section: Discussionsupporting
confidence: 54%
“… 29 , 30 Anemia can also induce oxidative stress through endothelial damage. 31 , 32 In our study, decrease in Hb level was strongly associated with the decrease in cognitive function of patients in the CI group as compared to patients without cognitive impairment. Pearson correlation analysis in our study showed that in ischemic stroke patients, the serum APN and Hb levels were positively correlated with MOCA scores, indicating a linear relationship between serum APN and Hb levels and vascular cognitive impairment severity.…”
Section: Discussionsupporting
confidence: 54%
“…9 Major causes of severe hemorrhage are pseudoaneurysm, arteriovenous fistula, and arterial laceration. 10 Venous bleeding can be controlled using conservative measures. Although the incidence of arterial hemorrhage is low, it can easily lead to hemodynamic instability, necessitating immediate intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This hemorrhage may occur immediately after the procedure or in the form of “delayed bleeding” which may occur after a few days. 6 The majority of patients settle with conservative management. However, a small proportion of patients requires intervention in the form of angioembolization.…”
Section: Introductionmentioning
confidence: 99%